Bergamottin reduces liver damage by suppressing inflammation, endoplasmic reticulum and oxidative stress in cafeteria diet-fed mice. (April 2023) - Yazıcı, Ebru; Şahin, Elif; Alvuroğlu, Elif; Yuluğ, Esin; Menteşe, Ahmet
Abstract: Cafeteria diet is known to induce excessive endoplasmic reticulum stress (ERS), oxidative stress (OS), and inflammation that could cause metabolic changes and liver diseases. Bergamottin (BGM) is a natural furanocoumarin that is known to have various biological activities. The present study, for the first time, assessed the reducing effect of BGM on the development of liver damage in cafeteria diet fed mice. 48 male C57BL/6 mice were fed an experimental diets diet for 16 weeks and BGM (0.05 mg/kg and 0.22 mg/kg) was administered for the last four weeks. The serum samples and liver homogenates were assessed for markers of ERS, OS, and inflammation. Also, histopathological analyzes were performed. This study demonstrated that the CAF diet caused metabolic changes, ERS, OS, and inflammation in serum and liver tissue. However, BGM exerts anti-oxidant, anti-ER stress anti-inflammatory effects in CAF-induced liver damage. Therefore, BGM may potentially be a novel therapeutic compound to ameliorate liver damage. Graphical abstract: Image 1